Prospects for the Use of Carbon Dioxide in Low-Temperature Devices for Cryogenic Technologies - Potapov, Volodymyr O.; Bilyi, Dmytro V. (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 165